SURVEY KAPASITAS TEKNIS STRUKTUR DERMAGA PELABUHAN LAMPIA - Chairul Paotonan; Muhammad Akbar Caronge; Ahmad Azwar (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2019)
Lampia Port is planned to be used by PT Sinergi Perkebunan Nusantara to ship its CPO (Crude Palm Oil). Before the plan is realized, it is necessary to conduct a study to determine the technical capacity of the pier structure. Therefore, in this study, a survey of the technical capacity of the pier was conducted to identify the condition of the existing pier structure. The survey includes measurements of the layout and dimensions of the pier structure, hummer test and carbonation test as well as visual observations. Based on the results of measuring the layout and dimensions of the pier, it was found that the shape of the pier is T-type consisting of a trestle with a length and width of 42.5 m and 6.0 m respectively and a pier with a length and width of 80.0 m and 10.0 m respectively. The number of piles for the trestle is 22 piles while for the pier is 64 piles. The pile diameter for trestle and pier is 508.3 mm. The hammer test results show that the concrete compressive strength of the pier structure ranges from K300-K400 which still meets the concrete requirements for the marine environment of K300. The carbonation test results show that the carbonation value is greater than 2.0 cm, so it is necessary to repair the concrete surface at least as deep as the carbonated area or as thick as the reinforcement concrete blanket. Visual observations show that the pier structure has not shifted but the beam and pile cap structures have experienced corrosion and carbonation.